Improving Reading Literacy Culture Through the Utilization of Reading Corners for Grade VII Students - Hendrikus Loy Bii; Ferdinandus Bate Dopo; Hermania Bupu; Melkior Wewe (Universitas Sulawesi Barat, 2025)
The purpose of this study was to foster a culture of reading literacy through reading corners for grade VII students at SMPS St. Petrus Lokatadho. This type of research is qualitative descriptive research. The subjects of this study were 30 grade VIII students of SMPS St. Petrus Lokatadho. The data collection methods used in this study were observation, interview and documentation methods. The data in this study were analyzed using the Milles and Huberman model data analysis technique consisting of 1) data collection, 2) data reduction, 3) data presentation and 4) drawing conclusions. The results of the study showed that through the use of reading corners, it had a positive impact on improving students' reading literacy culture. This was shown through an increase in the frequency of students' reading recorded in the questionnaire results after the reading corner was utilized optimally. Thus, it can be concluded that the reading corner plays an effective role as one of the strategies to improve the culture of reading literacy for grade VII students at SMPS St. Petrus Lokatadho.